Upaya Pemerintah Dalam Pembinaan Generasi Muda di Kelurahan Kakaskasen Dua Kota Tomohon - Gleydia Sefanya Mandagi; Apeles Lexi Lonto; Theodorus Pangalila (CV. Kurnia Grup, 2026)
This study aims to examine the government's efforts in fostering youth development, the obstacles encountered, and the solutions implemented in Kakaskasen Dua Village, Tomohon City. The main issue addressed in this research is the persistence of negative behaviors among youth, particularly alcohol abuse, which impacts public order. This study employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and questionnaires involving the village government, community members, and youth. The results indicate that the government’s efforts include socialization programs, collaboration with authorities, and youth activities. However, the implementation still faces several challenges, such as environmental influences, social media exposure, lack of parental supervision, and limited positive activities. Therefore, stronger collaboration and the enhancement of sustainable development programs are needed. In conclusion, youth development efforts have been carried out but are not yet optimal and need to be improved to produce responsible and well-characterized young generations